Vibrational and Normal Coordinate Analysis of Pyrazinamide - Gunasekaran, S.; Ponnambalam, U.; Muthu, S.; Ponnusamy, S. (Asian Journal of Chemistry, 2016)
A normal coordinate analysis on pyrazinamide has been carried out with a systematic set of symmetry coordinates following Wilson's F-G matrix method. The potential constant evaluated for the molecule is found to be in good agreement with literature values thereby confirming the vibrational assignments. To check whether the chosen set of vibrational frequencies contribute maximum to the potential energy associated with the normal coordinates of the molecule, the potential energy distribution has been evaluated.